Coal Consumption and Economic Growth in Turkey - Ocal, Oguz; Ozturk, Ilhan; Aslan, Alper (International Journal of Energy Economics and Policy, 2013)
This aim of this paper is to use asymmetric causality tests to examine the coal consumption and Gross Domestic Product (GDP) relationship in Turkey based on data from 1980 to 2006. To investigate this relationship, a multivariate system is employed by including fixed capital formation and labor force variables into the model. The empirical results obtained from asymmetric causality tests show no causality for coal consumption and GDP relationship in Turkey. The results indicate that coal consumption does not affect growth; hence, energy conservation policies may be pursued without adversely affecting growth in Turkey. Thus, neutrality hypothesis is confirmed for Turkey. This means that a decrease in coal consumption does not affect economic growth and vice versa. In this case, policymakers should explore the feasibility of either decreasing the coal consumption or increasing the efficiency of coal consumption. Keywords: Economic growth; coal consumption; asymmetric causality; Turkey JEL Classifications: O; Q43